2006
DOI: 10.1007/s00262-006-0248-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of adjuvant immunochemotherapy with polysaccharide K for patients with curative resections of gastric cancer

Abstract: Non-specific immunopotentiators, such as polysaccharide K (PSK), also known as OK-432, induce anti-tumor effects via immunological responses. The efficacy of combination immunochemotherapy using these immunopotentiators has been examined by multiple previous studies. The survival benefits of immunochemotherapy for patients with curative resections of gastric cancers are not widely accepted. To clarify this issue, we performed a meta-analysis to evaluate the effect of immunochemotherapy on survival in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 24 publications
1
56
0
1
Order By: Relevance
“…Those who took PSK showed a significant improvement in overall survival (RR 0.71; CI 0.55-0.90; P ¼ .006) and disease-free survival (RR 0.72; CI 0.58-0.90; P ¼ .003) [87]. Benefit of PSK was also demonstrated in a meta-analysis of 8,009 gastric cancer patients from eight randomized, controlled trials with an increased survival (HR 0.88; CI 0.79-0.98; P ¼ .0180) [88]. Specific clinical trials additionally cited an increase in disease-free survival rate for gastric cancer patients taking PSK with minimal toxicity [89].…”
Section: Immune Modulationmentioning
confidence: 90%
“…Those who took PSK showed a significant improvement in overall survival (RR 0.71; CI 0.55-0.90; P ¼ .006) and disease-free survival (RR 0.72; CI 0.58-0.90; P ¼ .003) [87]. Benefit of PSK was also demonstrated in a meta-analysis of 8,009 gastric cancer patients from eight randomized, controlled trials with an increased survival (HR 0.88; CI 0.79-0.98; P ¼ .0180) [88]. Specific clinical trials additionally cited an increase in disease-free survival rate for gastric cancer patients taking PSK with minimal toxicity [89].…”
Section: Immune Modulationmentioning
confidence: 90%
“…For example, Popiela et al [34] evaluated the effects of adjuvant immunochemotherapy with the use of bacillus CalmetteGuérin, and 5-fluorouracil, adriamycin, and mitomycin C, and reported a 24 % risk reduction in patients with stage III or stage IV gastric cancer after curative resection. Oba et al [35] performed a meta-analysis of immunochemotherapy with polysaccharide K for gastric cancer after curative resection, and reported a 12 % risk reduction. Fujimoto et al [36] reported the effects of postoperative adjuvant immunochemotherapy with the polysaccharide sizofiran on the same population, and concluded that curative resection of gastric cancer resulted in a better prognosis when sizofiran was prescribed along with the antitumor drug.…”
Section: Discussionmentioning
confidence: 99%
“…T. versicolor contains biologically active compounds with an enormous variety of chemical structures including the protein-bound PSP, B-1,3-B-1,4 glucans, tetracyclic triterpenoids of lanostane, fungisterol and B-sitosterol [10][11][12]. Furthermore, Polysaccharide-K (PSK) which can be obtained from mushrooms displays anticancer activity in laboratory studies and preliminary human researches [13,14]. Therefore, Trametes spp.…”
Section: Introductionmentioning
confidence: 99%